Synthesis and Characterization of Biodiesel Production from Wolffia Using Homogeneous KOH Catalyst by In Situ Transesterification - Saifuddin, S; Shalihah, Nyakty; Nahar, N.; N, Reza (Green Publisher Indonesia, 2023)
This research aims to analyze the quality and characteristics contained in biodiesels produced using Wolffia as the raw material with variations in weight of 200, 250, and 300 grams, and temperatures of 50ºC, 55ºC, and 60ºC. Furthermore, the biodiesel utilized in this study was made with reactants (Wolffia oil and methanol), fat solvent (n-hexane), and a heterogeneous catalyst (potassium hydroxide (KOH)). The results show that biodiesel formation was significantly impacted by temperature. Its volume increases with an upsurge in temperature and/or in raw materials, and the highest biodiesel product volume obtained was 81 ml. Following this, the product’s density value, which was 0.872 remained within the bounds of the SNI 04-7182:2015 standards, and the best calorific value was obtained from the biodiesel made with Wolffia, which was 9,754.70 cal/gr. Lastly, the maximum volume of Wolffia used was 300 grams, as this was the best composition to meet the SNI quality, and using the GC-MS analysis, the biodiesel’s quality was tested and found to contain methyl ester.